Justice and development in Latin America and the Caribbean (IDB WashingtonUS, 1994)
Looks at law, justice and development in Latin America in the nineties. Analyses topics such as the administration of the courts in the region: the judicial career and training; the issue of justice in times of globalization; justice and the internationalization of the law; and international cooperation in the area of administration of justice. Presents a comparative study of the administration of justice.
Seminar sponsored by the Inter-American Development Bank, San Jose, Costa Rica Feb. 4-6, 1993